2010
DOI: 10.1103/physrevb.82.224403
|View full text |Cite
|
Sign up to set email alerts
|

Impact of amorphization on the magnetic properties ofEuO-TiO2system

Abstract: Recently, we have reported amorphization-induced ferromagnetism in a magnetic oxide; whereas crystalline EuTiO 3 is an antiferromagnet, its amorphous counterpart shows a ferromagnetic transition. In this paper, we have investigated the magnetic properties of amorphous EuO-TiO 2 system in detail. The present compounds, i.e., amorphous EuTiO 3 and Eu 2 TiO 4 , exhibit a paramagnetic-ferromagnetic transition followed by a spin-glass transition upon cooling down, thereby being characterized as reentrant ferromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 38 publications
4
18
1
Order By: Relevance
“…It has been known that when an insulating magnet transforms from crystalline to amorphous phase, the magnetic transition temperature is usually suppressed because of the magnetic frustration, which is caused by the predominance of antiferromagnetic interactions and the random distribution of the magnetic ions . Nonetheless, we have recently observed interesting magnetic properties in amorphous EuO–TiO 2 system, definitely different from those of amorphous insulating magnets reported so far . For example, the amorphization of EuTiO 3 results in a switching from the antiferromagnetic to ferromagnetic state, and the ferromagnetic transition is observed at T c =5.5 K, which is comparable to the Néel temperature of antiferromagnetic c‐ETO.…”
Section: Introductioncontrasting
confidence: 60%
“…It has been known that when an insulating magnet transforms from crystalline to amorphous phase, the magnetic transition temperature is usually suppressed because of the magnetic frustration, which is caused by the predominance of antiferromagnetic interactions and the random distribution of the magnetic ions . Nonetheless, we have recently observed interesting magnetic properties in amorphous EuO–TiO 2 system, definitely different from those of amorphous insulating magnets reported so far . For example, the amorphization of EuTiO 3 results in a switching from the antiferromagnetic to ferromagnetic state, and the ferromagnetic transition is observed at T c =5.5 K, which is comparable to the Néel temperature of antiferromagnetic c‐ETO.…”
Section: Introductioncontrasting
confidence: 60%
“…It has been reported theoretically and experimentally that the magnetic ground state of EuTiO 3 crystal is critically balanced between antiferromagnetic and ferromagnetic ones, and a transition from antiferromagnet to ferromagnet could be realized by a lattice expansion [6][7][8][9]. More interestingly, our recent study demonstrated that amorphization of EuTiO 3 results in a switch of the magnetic ground state from antiferromagnetic to ferromagnetic one accompanied with an increase in the Weiss temperature (θ W ) [10,11]. This result is contrary to the usual understanding that the magnetic transition temperature is suppressed by amorphization.…”
Section: +mentioning
confidence: 88%
“…With decreasing T, an abrupt increase in M can be observed below 10 K, indicating a magnetic transition from paramagnetic to ferromagnetic phase. From the inflection point of M( T) curves, the ferromagnetic transition temperature (T C ) was estimated to be about 8 K, which is slightly higher than that of amorphous EuTiO 3 thin film [10,11]. As T is further lowered below T C , the M( T) curves for H dc = 20 and 50 Oe exhibit a discrepancy between those under ZFC and FC modes as shown in the inset of Fig.…”
Section: +mentioning
confidence: 93%
See 1 more Smart Citation
“…1 Instead, short-range antiferromagnetic (AFM) superexchange interactions via 2p states of oxide ions are predominant in the magnetic oxide glasses, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] with some exceptions such as Eu 2+ -containing glasses, where ferromagnetic (FM) interactions prevail. [19][20][21][22][23] In a system where magnetic moments are located at randomly distributed cations, the short-range AFM interactions inevitably bring about magnetic frustrations of geometrical origin. Consequently, SG phases appear at low temperatures due to the coexistence of randomness and frustration that are the key ingredients of SG.…”
Section: Introductionmentioning
confidence: 99%